Food insecurity among older, female African-Americans: a pilot project. Issue 1 (2nd January 2019) - Everhardt, Sharon Lindhorst; Bradley, Christopher; Cellon, Jonathan; Earnest, Samantha
ABSTRACT: Older African-American women living in the rural U.S. South are particularly vulnerable to food insecurity. This project used a one-group pretest–post-test research design to investigate if gardening and nutritional activities could be used as an effective intervention to reduce levels of food insecurity among this population. Statistical results found a significant reduction in food insecurity as a function of the intervention among the study respondents. Recommendations for future research include expanding the scope of study to different sites and climates with larger samples to enhance our understanding of the impacts of gardening and nutritional educational activities on food insecurity among older adults.